2012
DOI: 10.1177/0095798412461807
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Values Influencing Immigrant Haitian Mothers’ Attitudes Toward Human Papillomavirus Vaccination for Daughters

Abstract: Although research has shown that mothers significantly influence daughters' willingness to be vaccinated against the human papillomavirus (HPV), cultural factors influencing immigrant Haitian mothers' willingness to have adolescent daughters to be vaccinated are unknown. This is of concern as this population experiences disproportionately higher rates of HPV infection and related cervical cancers. This study identifies cultural beliefs influencing 31 immigrant Haitian mothers' willingness to vaccinate their da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 15 publications
0
31
0
10
Order By: Relevance
“…These measures however, may not be particularly effective given the social context in which their adolescents are being raised. Parents, therefore may engage in help-seeking behaviors, though these have generally been directed primarily towards family, rather than professionals, potentially reducing the effectiveness of corrective actions (27,32). Adapting and targeting interventions to address these needs requires that clinicians, particularly non-Haitian clinicians, should be knowledgeable enough of the culture to provide culturally competent care (58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These measures however, may not be particularly effective given the social context in which their adolescents are being raised. Parents, therefore may engage in help-seeking behaviors, though these have generally been directed primarily towards family, rather than professionals, potentially reducing the effectiveness of corrective actions (27,32). Adapting and targeting interventions to address these needs requires that clinicians, particularly non-Haitian clinicians, should be knowledgeable enough of the culture to provide culturally competent care (58).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that adolescents from minority cultures are often more vulnerable to engaging in risky behaviors; this vulnerability is related to residing in poor communities with a host of environmental risk factors (21,24,25). In these communities, associating with peers with high preventive norms and low traditional gender norms has been associated with less risky sexual behavior (27). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Qualitative studies suggested that these communication preferences were based on the perception that physicians were most knowledgeable about vaccines as well as patients' social and medical histories. [17][18][19][20] However, two studies indicated that preferences for talking with a physician about HPV vaccination lessened after initial discussions; respondents were more open to communicating with other providers or office staff for follow-up. 15, 21 The extent to which parent and patient preferences are currently being met is unknown; however, one recent study found that about half of physicians in a national sample did not make the initial HPV vaccine recommendation for patients in their practice, but rather relied on a nurse practitioner, medical assistant, or other provider to do so.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…4,[18][19][20]71,74,[76][77][78] However, the extent to which parents communicated about HPV vaccination beyond giving consent varied, with qualitative studies suggesting that parents from racial/ethnic minorities or with lower socioeconomic status were less likely to be engaged by providers and more likely than parents from more socially privileged backgrounds to defer to providers' advice. 19,71,73,74,77 Parents were also more likely to follow providers' advice without question when they received a strong, unambiguous recommendation.…”
Section: Communication Rolesmentioning
confidence: 99%